FreqChange: Frequency-aware spatiotemporal learning with prior guidance for semantic change detection in remote sensing images - Haiyan Huang; Zhenfeng Shao; Duowang Zhu; Xiao Huang; Ruiqian Zhang; Qimin Cheng; Jindou Zhang; Yueming Duan; Deren Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

High-throughput characterization of local structural imperfections in freestanding oxide membranes by lock-in thermography - Ao Wang; Jinfeng Zhang; Jinxiang Yan; Fang Xu; Qing Wang; Yueming Huang; Minghui Fan; Qiming Lv; Zhengguo Liang; Kunjie Dai; Dazhi Hou; Wenbin Wu; et al. (Science Bulletin, 2026)

Pharmacological inhibition of USP7 attenuates deltamethrin-induced neuronal ferroptosis via GPX4 stabilization - Minjia Wu; Yang Chen; Peixuan Ma; Wen Pan; Yaqin Deng; Lexing Wei; Guodong Lu; Michael Aschner; Yueming Jiang; Jing Zhou; Xiaowei Huang (Toxicology and Applied Pharmacology, 2026)

Apyrase MaAPY2 regulates the chilling tolerance of banana fruit as a negative modulator - Ying Li; Wanqi Chen; Shule Chen; Zhuojia Mao; Shihan Huang; Rufang Deng; Dandan Zhang; Taotao Li; Xuewu Duan; Yueming Jiang (Postharvest Biology and Technology, 2026)

Small-mammalian fossils from the Paleolithic Dayin Cave site in Yunnan, Southwest China - Yinan Zhang; Feng Gao; Yang Wan; Fan Yang; Bin Gao; Yueming Zeng; Bo Liu; Zetao Zhang; Wenwei Huang; Weiming Wang; Qiang Li; Xijun Ni (Quaternary International, 2025)

The impact of land use on the composition of dissolved organic matter and its relationship with microbes in a river basin in Northwestern China: Insights into microbial community structure and metabolic function - Xiang Zhu; Xinhua Gao; Yueming Zhu; Jingjie Huang; Fuquan Peng; Qingqing Pang; Fei Yang; Lei Xie; Zulin Hua; Longmian Wang (Journal of Environmental Management, 2025)

MEK1 inhibition ameliorates mitochondrial-dependent apoptosis induced by deltamethrin in mouse hippocampal neuron HT22 cells - Lexing Wei; Yang Chen; Minjia Wu; Peixuan Ma; Huan Wang; Yueming Jiang; Michael Aschner; Jing Zhou; Guodong Lu; Lina Zhao; Xiaowei Huang (Toxicology in Vitro, 2025)

Spatial extraction of sea-cucumber aquaculture ponds using remote sensing spectral and temporal features - Ruoqi Du; He Li; Chong Huang; Qingsheng Liu; Yueming Liu; Zhihua Wang (Frontiers in Marine Science, 2025)
The spatial distribution of aquaculture ponds plays a critical role in the layout, management, and evaluation of the aquaculture industry. While extensive research has been conducted on aquaculture pond extraction and monitoring, studies focusing on the differentiation of aquaculture ponds by species remain limited. The similar shapes and spectral features of water bodies associated with different species pose a challenge for extraction. A method for extracting sea-cucumber aquaculture ponds is proposed based on spectral temporal features using Sentinel-2 satellite imagery in this study. The method involves selecting the optimal sensitive spectral bands or combinations to construct two remote sensing indices of land-based aquaculture ponds. Using a time-series dataset of these indices, three key features—the mean and two slopes—are extracted. The corresponding time windows and thresholds for these key features are identified to develop a decision-tree algorithm for extracting sea-cucumber ponds. This method was applied to coastal aquaculture zones in Liaoning Province, China, to identify the spatial distribution of sea-cucumber aquaculture ponds in 2016 and 2023. The results showed that: (1) the proposed method achieved high extraction accuracy, with an overall accuracy of 79.24%; (2) Total area of sea-cucumber ponds in Liaoning Province was 931.08 km 2 , primarily located along the Huludao Xingcheng-Jinzhou Linghai and Yingkou Xishi-Dalian Zhuanghe coastal zones; (3) Over the past seven years, the area of sea-cucumber ponds increased by 624.57 km 2 , with expansion concentrated on the northwest coast of Liaodong Bay and both the eastern and western sides of the Liaodong Peninsula. These findings provide scientific support for the sustainable development of sea-cucumber aquaculture.

Stability analysis on the positioning of steel caisson foundations during submerging stage under complex marine conditions - Minglin Chen; Yong Xiao; Yueming Jin; Yonggan Sun; Bo Huang (Ocean Engineering, 2025)

The effect of resveratrol on lead-induced oxidative damage and apoptosis in HT-22 cells - Xiang Yi; Ruokun Wei; Shaoni Huang; Peiqi Wei; HuiShuai Li; Zhenning Li; Michael Aschner; Yueming Jiang; Shiyan Ou; Shaojun Li (Food and Chemical Toxicology, 2025)

Molecular characterization of large yellow croaker (Larimichthys crocea) coagulation factor Ⅶ-like and its function on macrophage proliferation and polarization - Yueming Chen; Han Zhao; Shuangshuang Cao; Hongjun Xie; Jieyu Huang; Xinhua Chen; Zhengwei Cui (Fish & Shellfish Immunology, 2025)

Improving the functional components and biological activities of navel orange juice through fermentation with an autochthonous strain Lactiplantibacillus paraplantarum M23 - Meiling Huang; Chunling Lai; Yan Liang; Qin Xiong; Chaoyun Chen; Zhiran Ju; Yueming Jiang; Jun Zhang (Food and Bioproducts Processing, 2025)

Interaction between root exudates and PFOS mobility: Effects on rhizosphere microbial health in wetland ecosystems - Bianhe Lu; Peifang Wang; Yueming Zhu; Jing Hu; Jin Qian; Yuanyuan Huang; Junwei Shen; Sijing Tang; Yin Liu (Environmental Pollution, 2025)

Association between exposure to arsenic, cadmium, and lead and chronic kidney disease: evidence from four practical statistical models - Jiongli Huang; Jingying Mao; Huilin Liu; Zhongyou Li; Guiyun Liang; Dabiao Zhang; Junchao Yang; Wen Qin; Pingjing Wen; Yueming Jiang; Zhaoyu Mo (Environmental Geochemistry and Health, 2025)

Fermentation by Penicillium polonicum improves the functional components and biological effects of orange peel via producing β-glucosidase without the risk of potential mycotoxins - Yan Liang; Chunling Lai; Liangliang Gao; Qingna Wu; Meiling Huang; Yueming Jiang; Jun Zhang (Food Bioscience, 2024)

Multi-rater Prism: Learning self-calibrated medical image segmentation from multiple raters - Junde Wu; Huihui Fang; Jiayuan Zhu; Yu Zhang; Xiang Li; Yuanpei Liu; Huiying Liu; Yueming Jin; Weimin Huang; Qi Liu; Cen Chen; Yanfei Liu; et al. (Science Bulletin, 2024)

Green and efficient approach to extract bioactive flavonoids with antioxidant, antibacterial, antiglycation, and enzyme inhibitory activities from navel orange peel - Chunling Lai; Meiling Huang; Qin Xiong; Yan Liang; Yueming Jiang; Jun Zhang (Sustainable Chemistry and Pharmacy, 2024)

Microbial colony sequencing combined with metabolomics revealed the effects of chronic hexavalent chromium and nickel combined exposure on intestinal inflammation in mice - Yueming Gu; Shuangyan Zheng; Cheng Huang; Xianhong Cao; Ping Liu; Yu Zhuang; Guyue Li; Guoliang Hu; Xiaona Gao; Xiaoquan Guo (Science of The Total Environment, 2024)

Discrimination and characterization of different ultrafine grinding times on the flavor characteristic of fish gelatin using E-nose, HS-SPME-GC-MS and HS-GC-IMS - Jinghong Xu; Zongcai Tu; Hui Wang; Yueming Hu; Pingwei Wen; Xiaoliang Huang; Shu Wang (Food Chemistry, 2024)

Control of citrus blue and green molds by Actinomycin X2 and its possible antifungal mechanism - Liangliang Gao; Yan Liang; Qin Xiong; Meiling Huang; Yueming Jiang; Jun Zhang (Pesticide Biochemistry and Physiology, 2024)

Forgone summertime comfort as a function of avoided electricity use - Minji Kwon; Shuchen Cong; Destenie Nock; Luling Huang; Yueming (Lucy) Qiu; Bo Xing (Energy Policy, 2023)

Inequalities across cooling and heating in households: Energy equity gaps - Luling Huang; Destenie Nock; Shuchen Cong; Yueming (Lucy) Qiu (Energy Policy, 2023)

Source Apportionment of Soil Heavy Metal(Loid)s in Farmland Using Diverse Models: A Comparative Assessment in the Yellow River Delta - Wei Huang; Shuhuan Wang; Lu Wang; Yingqiang Song; Yue Zhu; Hao Yang; Yingkai Xie; Yueming Hu (Journal of Marine Science and Engineering, 2023)
The rapid development of industrialization and urbanization has posed serious challenges for coastal farmland ecosystems. Source apportionment of soil heavy metals is an effective way for the detection of non-point source pollution in farmland to help support the high-quality development of coastal agriculture. To this end, 113 surface soil samples were collected in the coastal delta of China, and the contents of As, Cd, Cr, Cu, Ni, Pb, and Zn were determined. A variety of models were integrated to apportion the source of soil heavy metals, including positive matrix factorization (PMF), geographical detector (GD), eXtreme gradient boosting (XGBoost), and structural equation modeling (SEM). The result of PMF models revealed that there was collinearity between various heavy metals, and the same heavy metal may have a mixed source. The XGBoost model analysis indicated that there were significant non-linear relationships between soil heavy metals and source factors. A synergy between air quality and human activity factors was the key source of heavy metal that entered the study area, based on the results of the GD. Furthermore, the input path effect of heavy metals in the soil of the study area was quantified by SEM. The balance of evidence from the above models showed that air quality (SO2 and NO2) and factories in the study area had the greatest impacts on Cd, Cr, and Zn. Natural sources were dominant for Pb, while As, Cu, and Ni were contributed by soil parent material and factories. The above results led to the conclusion that there was a cycle path in the study area that continuously promoted the migration and accumulation of heavy metals in farmland soil; that is, the heavy metals discharged during oil exploitation and smelting entered the atmosphere and then accumulated in the farmland soil through precipitation, atmospheric deposition, and other paths. In this study, it is shown that a variety of models can be used to more comprehensively assess the sources of soil heavy metals. This approach can provide effective support for the rapid prevention and decision-making management of soil heavy metal pollution in coastal areas.

Heat transfer behavior of an immersed tube with sCO2 working fluid in a hot fluidized bed at high pressure - Yu Huang; Xu Bao; Yuanqiang Duan; Lin Li; Dongdong Fang; Yueming Wang; Lunbo Duan (Fuel, 2023)

RETRACTED ARTICLE: RINT1 is a new suppression target to reduce colon cancer cell growth, migration and invasion through regulating ZW10/NAG-1 expression - Jinheng Xu; Meng Zhao; Shunxian Huang; Qian Wu; Minghe Bai; Xueli Zhao; Jixian Wang; Yueming Hu; Junwei Feng; Zhiyong Zhang (Molecular and Cellular Biochemistry, 2022)

Establishment of Galectin-3 Time-resolved Fluoroimmunoassay and its Application in Idiopathic Membranous Nephropathy - Xiaomei Yu; Lingli Chen; Bo Lin; Li Zhang; Xue Yang; Xiaobin Liu; Pengguo Xia; Yueming Liu; Shaoxiong Zheng; Xiumei Zhou; Yigang Wang; Yuan Qin; et al. (Journal of Fluorescence, 2022)

Estimation of forest aboveground biomass by using mixed-effects model - Haoning Feng; Qi Chen; Yueming Hu; Zhiguo Du; Guantu Lin; Changwei Wang; Youju Huang (International Journal of Remote Sensing, 2021)

Phycocyanin fluorescent probe from Arthrospira platensis: preparation and application in LED-CCD fluorescence density strip qualitative detection system - Yunquan Zheng; Liuda Mo; Wenyi Zhang; Yunjian Duan; Jiandong Huang; Chengqun Chen; Yueming Gao; Xianai Shi; Feng Li; Jianmin Yang; Yanghao Guo (Journal of Applied Phycology, 2019)

A global survey of bacterial type III secretion systems and their effectors - Yueming Hu; He Huang; Xi Cheng; Xingsheng Shu; Aaron P. White; John Stavrinides; Wolfgang Köster; Guoqiang Zhu; Zhendong Zhao; Yejun Wang (Environmental Microbiology, 2017)
Summary The type III secretion system (T3SS) is an important genetic determinant that mediates interactions between Gram‐negative bacteria and their eukaryotic hosts. Our understanding of the T3SS continues to expand, yet the availability of new bacterial genomes prompts questions about its diversity, distribution and evolution. Through a comprehensive survey of ∼20 000 bacterial genomes, we identified 174 non‐redundant T3SSs from 109 genera and 5 phyla. Many of the bacteria are environmental strains that have not been reported to interact with eukaryotic hosts, while several species groups carry multiple T3SSs. Four ultra‐conserved Microsynteny Blocks (MSBs) were defined within the T3SSs, facilitating comprehensive clustering of the T3SSs into 13 major categories, and establishing the largest diversity of T3SSs to date. We subsequently extended our search to identify type III effectors, resulting in 8740 candidate effectors. Lastly, an analysis of the key transcriptional regulators and circuits for the T3SS families revealed that low‐level T3SS regulators were more conserved than higher‐level regulators. This comprehensive analysis of the T3SSs and their protein effectors provides new insight into the diversity of systems used to facilitate host‐bacterial interactions.

Water loss from litchi (Litchi chinensis) and longan (Dimocarpus longan) fruits is biphasic and controlled by a complex pericarpal transpiration barrier - Markus Riederer; Katja Arand; Markus Burghardt; Hua Huang; Michael Riedel; Ann-Christin Schuster; Anna Smirnova; Yueming Jiang (Planta, 2015)